Targeting Sedentary Behavior in Minority Populations as a Feasible Health Strategy during and beyond COVID-19: On Behalf of ACSM-EIM and HL-PIVOT. Issue 4 (17th September 2021) - Lassalle, Patricia Pagan; Meyer, Michelle L.; Conners, Ryan; Zieff, Gabriel; Rojas, Jacklyn; Faghy, Mark A.; Arena, Ross; Vermeesch, Amber; Joseph, Rodney P.; Stoner, Lee
ABSTRACT: Increased sedentary behavior has been an unintended consequence of social and physical distancing restrictions needed to limit transmission of SARS-CoV-2, the novel coronavirus that causes COVID-19. Sedentary behavior is defined as any waking behavior characterized by an energy expenditure ≤1.5 METs while in a sitting, reclining, or lying posture. These restrictions negatively affect peoples' cardiometabolic and mental health and disproportionately affect certain sectors of the population, including racial/ethnic minorities. In part, the higher risk for complications of COVID-19 could be the result of an increased prevalence of comorbid diseases. Further, regular participation and adherence to current physical activity guidelines, defined as at least 150 min·wk −1 of moderate-intensity physical activity or muscle strengthening activities on 2 or more days a week, is challenging for many and may be especially difficult to achieve during the COVID-19 pandemic. A practical strategy to promote health and well-being during COVID-19 is reducing sedentary behavior. Reducing sedentary behaviors (e.g., breaking up periods of prolonged sitting with light-intensity physical activity) may be more easily achieved than physical activity for all individuals, including individuals of racial/ethnic decent, as it does not require purchasing equipment nor require compromising the physical restrictions necessary to slow the spread of COVID-19. The purpose of this commentary is to argue that sedentary behavior is a feasible, independent target to modify during COVID-19, particularly in minority populations, and to address this behavior we need to consider individual, environmental, and policy-level factors.